Pengembangan Ecovillage yang Berkelanjutan pada Lanskap Ciboleger Kaduketug 1 Baduy Luar - A’la, Yava Ar Rafiqu; Simangunsong, Nur Intan; Fauzi, Reza; Fitri, Rini; Setiawan, Eko Adhy (Jurnal Lanskap Indonesia, 2025)
Amid increasing pressures from tourism and modernization threatening the cological and cultural integrity of the Baduy Luar community, this study explores the development of an ecovillage landscape in Ciboleger-Kaduketug 1, Baduy Luar. The focus is on sustainable practices that align with local cultural values. The objective is to establish a model that preserves indigenous knowledge while enhancing ecological resilience, cultural continuity, and economic viability in the region. A quantitative and descriptive approach was applied. The research involved field observations, semi-structured interviews with purposively selected key informants, including community leaders, elders, and active practitioners of Baduy traditions, as well as literature analysis. The sample included key ecological elements (e.g. endemic vegetation) and cultural-economic actors, with purposive sampling used based on knowledge relevance and social roles. Results indicate high ecological sustainability (97%), supported by native vegetation and traditional land-use practices that demonstrate the community effective ecological stewardship. Social and cultural sustainability scored lower (48%) due to external influences impacting traditional lifestyles, indicating an urgent need for strategies that strengthen cultural identity and traditional governance. Economic sustainability achieved a relatively high score (86%), with opportunities identified in eco-cultural tourism, local crafts, and agroforestry-based income streams. These findings form the empirical basis for a proposed ecovillage development model, structured around culturally grounded spatial zoning, resource governance, and integrated livelihood strategies. The study contributes to sustainable rural development literature by offering a site-specific, replicable model for indigenous communities that harmonizes environmental stewardship with cultural and economic resilience. This model presents valuable insights for other rural and traditional communities aiming to achieve sustainability without compromising cultural heritage.